Resesrch methods for business a skill-building approach - Sekaran, Uma (Wiley, 2000)
Ethical issues relating to research and the aspects of business, data collection, and data analysis are integrated throughout the book. * The issues in cross-national research in sampling and data collection are thoroughly discussed. * The qualitative-quantitative aspects of research are brought together through a case study on the final chapter.